A retrospective study of outcomes after referral to the early intervention in psychosis programme at Valkenberg Psychiatric Hospital - Setjie, Sewela (Department of Psychiatry and Mental Health, 2023)
Background. Psychotic Disorders affect more than 1% of the South African adult population and have a chronic course that is associated with high rates of morbidity and mortality. The implementation of early intervention strategies may reduce the severity of these disorders. Little is known about the effectiveness of these interventions in South Africa and few longerterm studies have been undertaken internationally. Aim. This study aimed to measure the effectiveness of an Early Intervention and Support (EISH) service at reducing readmission to hospital in patients with psychotic disorders. Setting. Valkenberg Psychiatric Hospital, Cape Town. The EISH Team is an outpatient service consisting of psychiatrists, a psychologist, an occupational therapist, psychiatric nurses and social workers. Methods. Retrospective cohort study. Hospitalisation during the two years after discharge from the index admission was measured in 100 subjects who attended EISH and 100 who had treatment as usual (TAU). Readmission rate, average length of stay (ALOS), and time to readmission to District Hospitals (DH) and Tertiary Psychiatric Hospitals (TPH) were calculated. Results. Readmission Rates were three times higher in TAU compared to EISH patients for both types of Hospital. For TAU subjects compared to EISH subjects: ALOS was longer (59 vs 13 days), and days to readmission were fewer (187 vs 320 days). All differences were statistically significant (ps < .05). Conclusion. EISH intervention at Valkenberg Hospital was useful in reducing readmission rate, ALOS, and time to readmission in patients with Psychotic disorders. Prospective controlled trials are required to confirm the efficacy of this intervention.